HUBUNGAN PENANGANAN SAMPAH KOTA DENGAN PERILAKU MASYARAKAT : Studi Kasus Pengelolaan Sampah Kota Cimahi - Ruslan Ramang (Environmental Research Center (PPLH) of Udayana University, 2013)
AbstractThis article aims to look at find out the existing condition of the way the community hanldetheir wastes, at the level of household, to analyse points which back the communityparticipation, having constrains of the handling of the existing wastes and waste-relatedproblems which the community of the respective city face. The questionaire-based survey,was engaged into the research as the survey method while the stratified random samplingwas engaged throughout the analysis of the same as the sampling technique. The resultsshows that existence of an operational public waste collecting system tends to lessen thewaste-related problem in the respondents’ residential enviroment. Four factors whichdifferentiate the respondents who participate from those who do not, in respect to wastetreatment are: behaviour of disposing waste to river, behaviour of burrying the wastes, theproblem of smell and the problem of river pollution. Existence of a good public wastecollecting system which can overcome the waste-related problems in the residentialenvironemnt of the community, can motivate the same to participate in better treating andmanage their wastes.